Dinamika Peluncuran IDX Carbon dan Intensifikasi Isu Hilirisasi terhadap Industri Tambang di Indonesia - Athallah, Renzo Romero; Arieftiara, Dianwicaksih (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to explore the impact of the IDX Carbon launch and the issue of downstream processing on the mining industry' in Indonesia, with a focus on how these initiatives influence investor sentiment and the industry Methodology/approach: The research employed a quantitative approach using statistical analysis of data from mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The study utilized STATA 17 software and Structural Equation Modelling (SEM) to examine the relationships between variables Results/findings: The findings reveal that both IDX Carbon and hilirisasi initiatives do not significantly impact mining companies. This is attributed to the inability to effectively represent investor sentiment or alter market perceptions during the study period. Additionally, the research identified a feedback loop where a company's value influences investor perceptions that resulting in a paradox. Limitations: The study is limited by its focus and specific timeframe analyzed, which may not capture the potential effects of the IDX Carbon launch and downstream policies. Contribution: This study adds to the literature on environmental policies, industrial transformation, and financial market behavior, offering insights for investors, and corporate decision-makers in the mining sector.